A method for emergency response alternative decision-making under uncertainty. Issue 4 (2nd October 2021) - Xia, Dengyou; Li, Chengyao; Xin, Jing; Zhu, Yi
Abstract : In this paper, an emergency decision-making method, based on case-based reasoning and cloud model, is proposed to solve the risk decision-making problem in emergency response. Case-based reasoning, by allowing the decision-maker to referring to past decisions, introduces a short-cut to formulate feasible emergency alternatives. Cloud model is used to evaluate and optimise the emergency response alternatives. To evaluate emergency response alternatives, the decision criterion must be determined according to the aim and characteristics of emergency rescue in disasters or accidents. Then, the weight cloud and evaluation cloud of the decision criterion are determined by the Delphi method combined with backward cloud generator, and the synthesised cloud of each alternative is calculated through arithmetic rules of cloud. Finally, a ranking of all response alternatives can be determined, and the best alternative is selected. Case study shows that the method makes the conversion between qualitative description and quantitative indication more effective.